Politics in the vernacular : nationalism, multiculturalism, and citizenship - Kymlicka, Will. (Oxford, UK New York : Oxford University Press, 2001)
"This volume brings together eighteen of Will Kymlicka's recent essays on nationalism, multiculturalism and citizenship. These essays expand on the well-known theory of minority rights first developed in his Multicultural Citizenship. In these new essays, Kymlicka applies his theory to several pressing controversies regarding ethnic relations today, responds to some of his critics, and situates the debate over minority rights within the larger context of issues of nationalism, democratic citizenship and globalization."--BOOK JACKET.
16. Education for Citizenship -- 17. Citizenship in an Era of Globalization: Commentary on Held -- 18. Liberal Egalitarianism and Civic Republicanism: Friends or Enemies?
Includes bibliographical references (p. [347]-366) and index.
Keywords: Minorities -- Civil rights; Liberalism; Nationalism; Internationalism; Multiculturalism; Citizenship